Hometown recipes for the holidays / Candace Floyd,...[et al.] - Anne GillemAuthor
Offers over two hundred fifty recipes for American holidays held and celebrated throughout the year, including Easter, Father's Day, and Thanksgiving, along with illustrations and tips for starting a family tradition.